Tinjauan Penerapan Sistem Manajemen Keselamatan Dan Kesehatan Kerja (Smk3) (Studi Kasus : Proyek Pembangunan Gedung Menara BRI Pekanbaru) - Orilian, Anestia; Iriana, Rian Tri Komara; Sebayang, Mardani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Pekanbaru is one of the cities that has high number level development in Indonesia. To support Banking business facility in Pekanbaru, Bank Rakyat Indonesia (BRI) built BRI tower which is located in Sudirman Street Tangkerang Tengah, Pekanbaru. BRI tower project hired 171 workers and uses heavy equipments so it would risk safety and comfort of the workers. To decrease the number of work accidents and to apply ‘zero accident’ so it’s needed to apply safety and health management system in this project. The purpose this research is to observe safety and health management system in this project. The researcher used qualitative method, analysis unvariate, and descriptive quantitative method. The questionnaire has been spread through some respondents, 149 construction workers and 22 project staffs. The result of assessment in applying safety and health management system based on PP No.50 Tahun 2012 showed that it reaches 60% and it belongs to Good rate. The result of audit safety and health management system BRI tower Pekanbaru project reaches 100% and it belongs to Excellent rate. According to analysis of safety and health equipments cost calculation, it shows Rp 721.485.925,00 or 0,5% from the total of project contract value and it’s already fulfilling PT Pembangunan Perumahan rules which requires safety and health procurement budget worth 0,5%-1% for ≤ Rp 300 billions project value. Some factors that obstruct safety and health management system applying are workers psychological and environmental factors.Keywords: Safety and Health management system, BRI Tower, PP No.50 tahun 2012